PERANAN PERBANKAN DALAM MENINGKATKAN PEREKONOMIAN INDONESIA - H. Bachtiar Simatupang (Universitas Islam Islam Sumatera Utara, 2020)
Indonesia as a developing country aims to achieve a fair and prosperous society, evenly material and also spiritual. As a country with a goal and strategy, Indonesia is implementing a lot of things to do to improve Indonesia's mature economy along with equitable development spread throughout the archipelago. BUMN is one of the national economy drivers. Banking as one of the State enterprises in implementing its operations is not solely to seek profit, but should support the Government's efforts in enhancing the national economy. It is expressly stated in article 4 of the Republic of Indonesia Law number 7 year 1992 concerning banking mentions: